2013
DOI: 10.1163/22125868-12340023
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Student Engagement and Outcomes: Modelling Insights from Australia and Around the World

Abstract: Assessing how students engage and what they know and can do are pressing change frontiers in contemporary higher education. This paper examines large-scale work that has sought to advance the capacity of higher education systems and institutions to engage students through to graduation and ensure they have capabilities required for future study or work. It reviews contexts fuelling the importance of engagement and learning outcomes, reviews two large-scale case studies, and advances a broad model for structuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The second dimension of the ATM is underpinned by activity , which comprises five stages: anarchic, appreciation, articulation, application, and amalgamation. This dimension reflects a continuum of increasing sophistication in the scope and scale of the relevant activities, which encourages controlled collaboration (Coates & Mahat, 2013).…”
Section: The Atmmentioning
confidence: 99%
“…The second dimension of the ATM is underpinned by activity , which comprises five stages: anarchic, appreciation, articulation, application, and amalgamation. This dimension reflects a continuum of increasing sophistication in the scope and scale of the relevant activities, which encourages controlled collaboration (Coates & Mahat, 2013).…”
Section: The Atmmentioning
confidence: 99%
“…Recent research and theory has suggested that a conceptually and psychometrically sound measure of student engagement is necessary for the measurement of student engagement (Coates & Mahat, 2014). In previous investigations, both the NSSE and the AUSSE engagement scores have demonstrated adequate reliability and validity evidence for the five-factor model of student engagement based on large-scale datasets (Coates, 2011; Pascarella, Seifert, & Blaich, 2010).…”
Section: The Student Engagement Scalementioning
confidence: 99%
“…Research shows that student engagement has an important effect on students’ academic experiences and overall outcome of university education (Coates & Mahat, 2014; Pascarella et al., 2010). Moreover, three decades of evidence suggest that student engagement, that is students dedicating their time and energy to educationally purposeful activities, is a significant predictor of their satisfaction and attainment of multiple educational outcomes of university (Ko, 2011; Pascarella & Terenzini, 1991, 2005; Wefald & Downey, 2009).…”
Section: The Student Engagement Scalementioning
confidence: 99%
“…The concern of this paper is student engagement in higher education. In fact, a focus on student engagement in higher education research is very important because engagement has shown to be a key contributor to student learning (Coates and Mahat, 2014;Pascarella et al, 2010). Research evidence suggests that student engagement, that is, students dedicating their time and energy to learning purposeful activities, is a significant predictor of their satisfaction and attainment of multiple learning outcomes in higher education (Almarghani and Mijatovic, 2017;Wefald and Downey, 2009).…”
Section: Introductionmentioning
confidence: 99%